A critical appraisal of the recent IFCC statements on cardiac troponin assays - Giannitsis, Evangelos; Müller-Hennessen, Matthias (Clinical chemistry, 2017)
To the Editor: We read with interest the Mini-Review on cardiac troponin assays published by the IFCC Task Force on Clinical Applications of Cardiac Bio-Markers (1). We feel that important statements on analytical issues related to high-sensitivity troponin (hsTn)1 and particularly hsTnT are unsupported by scientific evidence and need critical reappraisal. First, Tables 1 and 2 in the Mini-Review listing the analytical performance of hsTn assays do not cite the source of the information. It appears that analytical performance data and reference intervals were most likely derived from a single reference population of presumably healthy volunteers instead of an overview of available data (Mini-Review Table 1) including those in the package insert of hsTnT that is based on a multinational multicenter evaluation (2). The reference population listed in the Mini-Review suffers from 3 weaknesses. First, classification as “healthy” is not objectively determined by clinical or functional testing, nor by biomarker phenotyping. Second, the reference population does not meet the sample size criteria of at least 300 males and 300 females as set by IFCC itself (1). Third, sample …